2009
DOI: 10.1007/s11096-009-9314-z
|View full text |Cite
|
Sign up to set email alerts
|

Medication review and patient counselling at discharge from the hospital by community pharmacists

Abstract: Aims In 2001, the Association of Amsterdam Community Pharmacists adopted a programme to improve the pharmaceutical care of patients who were discharged from hospital with five or more drug prescriptions. A comprehensive protocol for pharmaceutical care at discharge (IBOM-1) was developed. The aim of the study was to evaluate the initial IBOM protocol and to study the effects of the protocol on drug therapy and patient satisfaction as well as on drug use compliance and mortality. Method A controlled interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 18 publications
(23 reference statements)
0
45
0
1
Order By: Relevance
“…Recent studies indicated that pharmacist-conducted medication review and home visits are potentially beneficial [3,[8][9][10][11][12] but some randomised controlled trials failed to prove effectiveness [13][14][15][16]. It remains an open question if for particular diseases, tailored medication reviews by specifically trained pharmacists are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicated that pharmacist-conducted medication review and home visits are potentially beneficial [3,[8][9][10][11][12] but some randomised controlled trials failed to prove effectiveness [13][14][15][16]. It remains an open question if for particular diseases, tailored medication reviews by specifically trained pharmacists are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Medication review carried out by a pharmacist has been shown to be an effective service to identify DRPs [3,9,10,[17][18][19][20]. However, not all DRPs can be detected by a review in the pharmacy [17].…”
Section: Introductionmentioning
confidence: 99%
“…Eight articles were selected for the review. Seven articles specifically explored approaches to improve seamless care focusing on medication [14][15][16][17][18]20]. In addition, one study described the study protocol for an economic evaluation, but did not present any results [21].…”
Section: Search Resultsmentioning
confidence: 99%
“…All but one study carried out an economic evaluation based on a randomized controlled trial [14,16,18,20] or an observational study [15,17,21]. Investigating the costeffectiveness of treatment alternatives in a trial setting provides a degree of internal validity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation